Differential cardiovascular profiles of sodium-glucose cotransporter 2 inhibitors: critical evaluation of empagliflozin - Sanon VP; Patel S; Sanon S; Rodriguez R; Pham SV; Chilton R (Dove Medical Press, 2017)
Vani P Sanon,1 Shalin Patel,1 Saurabh Sanon,2 Ruben Rodriguez,1 Son V Pham,1 Robert Chilton1 1Division of Cardiology, University of Texas Health Science Center at San Antonio, Audie L Murphy VA Hospital, San Antonio, TX, 2Interventional Cardiology-Structural Heart Disease, Cardiology Consultants at Baptist Heart and Vascular Institute, Pensacola, FL, USA Abstract: One of the most feared repercussions of type 2 diabetes mellitus is the risk of adverse cardiovascular outcomes. The current antidiabetic agents on the market have had difficulty in showing cardiovascular outcome improvement. The EMPA-REG OUTCOME trial studied the sodium-glucose cotransporter 2 inhibitor empagliflozin in type 2 diabetic patients at high risk of cardiovascular events. The trial results revealed a decrease in the composite primary end points of death from cardiovascular causes, nonfatal myocardial infarction, and nonfatal stroke in those taking empagliflozin vs placebo. Those taking the medication also had a significant decrease in death from any cause, death from cardiovascular cause, and hospitalization for heart failure. The EMPA-REG trial is paradigm shifting because it demonstrates a clear mortality benefit to cardiovascular outcomes with a low side-effect profile, in contrast to prior outcome studies of hypoglycemic agents. Further studies are required to better clarify the long-term safety and efficacy of this promising class of diabetic drugs. Keywords: SGLT2 inhibitors, diabetes, cardiovascular mortality, heart failure, hypertension